Maternal Postpartum Depression Consequences towards Mother-child interaction Outcomes: A Systematic Review - Muhammad Bardan Hanif (Scientia Psychiatrica, 2021)
Postpartum depression is a psychiatric disorder that starts from the second to the sixth week after birth. Postpartum depression has been shown to have an association with infant growth, nutrition, bonding, temperament and ultimately childhood mental wellbeing. This paper reviews overall outcomes of untreated maternal postpartum depression towards the mother-child interactions consequences. Systematic review was conducted in the online databases Google Scholar and PubMed using the index terms “postpartum depression” and “maternal outcomes” or “children outcomes”. Total of 10 studies (out of 112 references retrieved from bibliographic databases) were included in this systematic review. The results of the studies were synthetized into mother–child interactions, including bonding, breastfeeding, and the maternal role. The results suggest that postpartum depression creates an environment that is not conducive to the mother-child interaction thus regressing personal development of mothers or the optimal development of a child. It therefore seems important to detect and treat depression during the postnatal period as early as possible to avoid harmful consequences.